Effect of Vitamin D on children with allergic bronchitis - AL-Khalidy, Marwan Khalid Mohammed; Al-doori, Alaa Zanzal Raad (International Journal of Psychosocial Rehabilitation, 2020)
Back ground: This study was done to detect the level of vitamin D in children infected with allergic bronchitis. Aim: The aim of this study is to evaluate the relation between allergic bronchitis in children with low level of vitamin D. Study Design: Case-control study. Patient study: This study was performed in Mosul city from January 2019 to June 2019. The total number of children in this study was 200 (152 patients and 48 control) were recruited from the emergency department, outpatients clinics of Ibn al-Atheer teaching hospital for children, pediatric private clinic and from primary schools of children in Mosul city. The sample size was 152 patients with allergic bronchitis (109 males and 43 females) whose age between 1-15 years, while the control group who were matched to the patients, included 48 children (38 males and 10 females), all of them were healthy children (no sign and symptoms of allergic bronchitis), they were not received any medication, with no history of allergic bronchitis or acute illness. Methods: 10 ml of blood were collected by vein puncture using dispossible syringe from each patients and control enrolled in this study for determination of vitamin D levels using enzyme linked immune-sorbent assay (ELISA technique), also throat swab samples were taken from both patients and controls and placed in a screw caped tube containing a transport media, after that the swab cultured on blood, MacConkey, and chocolate agar for (18-24) hours at 37˚C to see and detect the causative agents of bronchitis in children. Result: Vitamin D levels was significantly lower in allergic bronchitis patients and even in control cases. Conclusion: There is an important association between children allergic bronchitis and vitamin D deficiency or even insufficiency in both patients and control cases.